Evaluation of ESG Ratings for Chinese Listed Companies From the Perspective of Stock Price Crash Risk - Li, Sicheng; Yin, Pengfei; Liu, Shuai (Frontiers in Environmental Science, 2022)
ESG investment strategy has attracted increasing attention from the financial market, and the inconsistency of enterprise ESG rating results of different rating agencies has gradually become the focus of attention of regulators and investors. In this paper, the listed companies with ESG ratings in Shanghai and Shenzhen A-shares from 2016 to 2020 were selected as the research samples. Combined with DID and OLS methods, the rationality of these ESG ratings was evaluated by examining the difference in the impact of three international ESG rating agencies such as Bloomberg and three Chinese ESG rating agencies such as Sino-securities on the stock price crash risk. The research finds that: First, after incorporating the ESG ratings of FTSE Russell, MSCI and China Alliance of Social Value Investment, the stock price crash risk of enterprises is significantly reduced. Secondly, the better the ESG evaluation results of Bloomberg and MSCI, the lower the stock price crash risk. Third, compared with social indicators, investors pay more attention to the environmental performance of enterprises in decision-making. Enterprises with high environmental scores have lower stock price crash risk. The findings of this paper play an enlightening role for China to improve its ESG system, construct ESG disclosure policy and improve the market role of ESG rating.